Effect of Economic Indicators, Renewable Energy Consumption and Human Development on Climate Change: An Empirical Analysis Based on Panel Data of Selected Countries - Hao, Yuanyuan (Frontiers in Energy Research, 2022)
Global warming is mainly influenced by factors such as energy consumption, human development, and economic activities, but there is no consensus among researchers and there is relatively little research literature on less developed countries. Therefore, this study attempts to explore the impact of renewable energy consumption, human development and economic growth on climate change from a macroeconomic perspective for 105 countries worldwide over the period 1990-2019 by constructing a panel vector autoregressive (PVAR) model and using generalized method of moments (GMM) and panel impulse response analysis. The analysis includes four panels of high-income, upper-middle-income, lower-middle-income, and low-income countries. The results of the study find that economic growth, FDI, trade openness, industrialization, renewable energy consumption and HDI have different impacts on climate change (CO2 emissions) in different regions during the sample period. Specifically, in the four panels, economic growth, industrialization, FDI, and trade openness all play a varied role in aggravating environmental pollution (CO2 emissions). In high-income and upper-middle-income countries, industrialization has a positive effect on CO2 emissions, while FDI has a negative impact, which supports the pollution halo hypothesis. However, both have a positive impact on CO2 emissions in lower-middle-income and low-income countries. The results also found that except for upper-middle-income countries, trade openness and renewable energy consumption help reduce CO2 emissions, while renewable energy consumption has little effect on suppressing CO2 emissions in low-income countries. In addition, HDI has promoted CO2 emissions in upper-middle-income and lower-middle-income countries, but has curbed CO2 emissions in high-income countries. Therefore, under the premise of not affecting economic growth and HDI, those empirical results will not only help decision-makers formulate appropriate renewable energy policies, but also are of great significance to the realization of a healthy and sustainable global environment.